COMPARATIVE ASSESSMENT OF SOIL PROPERTIES IN ORGANIC, CONVENTIONAL, AND ABANDONED VEGETABLE CULTIVATION SYSTEMS IN VEGETABLE-GROWING AREAS OF HANOI - Ha Linh, Nguyen; Thi Hong Lien, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
The application of fertilizers and agrochemicals in crop cultivation can significantly affect the physicochemical properties and nutrient composition of vegetable soils. In this study, soil samples were collected from eighteen vegetable fields managed under organic farming, conventional farming, and abandoned land-use systems across four specialized vegetable-producing communes in southern Hanoi. Results indicated that the cultivated soils were mainly loamy and sandy loam soils, both suitable for vegetable production. Physical, chemical, and nutrient parameters varied among cultivation systems. Organic farming soils showed the best quality in terms of physicochemical properties, organic matter content, and macro- and micronutrient contents. Conventional farming soils contained higher concentrations of macro- and micronutrients compared to abandoned fields, but exhibited lower organic matter content. Organic farming soils have BD: 1.08 g/cm3, PD: 2.62 g/cm3, OC: 1.34%, N: 0.12%, P2O5: 0.21%, K2O: 0.95, CEC: 13.07 cmol/kg of air-dried soil. Conventional farming soils exhibited BD: 1.18 g/cm3, PD: 2.47 g/cm3, OC: 1.09%, N: 0.10%, P2O5: 0.35%, K2O: 0.74, CEC: 11.87 cmol/kg of air-dried soil. The cultivation of organic vegetables not only ensures a safe and health-promoting food supply for humans but also contributes to environmental protection and the improvement of soil quality. This practice represents a sustainable approach to soil utilization and should be actively promoted for wider adoption.